Detection of fimA & fimC genes of Salmonella Typhimurium isolated from different sources - mayar hazam, Abbas; Ghaly Yousif, Maitham (Al-Qadisiyah Journal of Pure Science, 2018)
The collection of 500 different sample for the purpose of investigating the bacterium Salmonella typhimurium as included 140 stool specimens from children, male and female who admitted to the Teaching Hospital of Maternity and Pediatrics, in Al-Diwaniya ,90 a sample of stool pigeons ,142 a sample of the liver freezer and 128 sample of frozen meat examined in the laboratory of public health in Diwaniya, a laboratory of the Central Health in Baghdad.. The results of culturing on selective media, in addition to API 20 E system revealed that the rate of Salmonella isolates was (54/500)10.8% . results of serotyping Salmonella isolates by using monovalent antisera revealed that 50 out of 54 isolates (92.6 %) belong to S .typhimurium. Polymerase chain reaction (PCR) was used to detect fimA gene encoding for biosynthesis of fimbriae A of S. typhimurium and fimC gene encoding for fimbriae C of S. typhimurium, PCR technique revealed that 5092.6%) ) isolates of S. typhimurium. were contain fimA and fimC gene.